Rethinking on Drug Abuse and Crime Relationship: An Alternative Explanation for Intellectuals Criminologists - Karofi, Usman Ahmad (Mediterranean Journal of Social Sciences, 2012)
According to the literature on the drug-crime link, there is relationship between abusing drugs andinvolvement criminal activities. A growing number of literature and empirical research have documentedthat relationships exists between drug abuse and criminal offences. Through studying a selected sample ofthree hundred institutionalised drug addicts [inmates] with and without criminal history from twogovernment drug rehabilitation centres in Penang, Malaysia, findings from an empirical research affirmedthat indeed relationships exist between drug abuse and involvement in criminal offences. The result of thestudy reveals that is not in all situation abusers of drugs get involved in criminal activities, even in situationwhere they do so, abusing the drug alone is inappropriate in justifying their attitudes. In addition toabusing drugs other micro and macro factors should be put in place for proper understanding of theircriminal offences.